The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1524-4741.2006.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

New Antineoplastic Agent, MK615, from UME (a Variety of) Japanese Apricot Inhibits Growth of Breast Cancer Cells in vitro

Abstract: MK615 is an extract mixture containing hydrophobic substances from Japanese apricot. In this study, the antineoplastic effects of MK615 against breast cancer cells were investigated. Two breast cancer cell lines, MDA-MB-468 (MDA) and MCF7, were cultured with (600, 300, and 150 mug/mL) or without MK615. After 72 hours of incubation, growth inhibition was evaluated by MTT assay. The cells were then cultured with MK615 (300 mug/mL) and morphological changes were studied by light and electron microscopy. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 14 publications
2
37
2
2
Order By: Relevance
“…Previous studies have revealed that MK615 has anti-neoplastic effects against gastric cancer [1] , breast cancer [2] , hepatocellular carcinoma [3] , and colon cancer [4] . The mechanisms responsible for the anti-neoplastic effect of MK615 include induction of apoptosis [1,2] and autophagy [4] , and suppression of Aurora A kinase [3] in cancer cells. However, the entire mechanisms of the anti-neoplastic effects of MK615 have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that MK615 has anti-neoplastic effects against gastric cancer [1] , breast cancer [2] , hepatocellular carcinoma [3] , and colon cancer [4] . The mechanisms responsible for the anti-neoplastic effect of MK615 include induction of apoptosis [1,2] and autophagy [4] , and suppression of Aurora A kinase [3] in cancer cells. However, the entire mechanisms of the anti-neoplastic effects of MK615 have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…MK615 is a compound made by condensing and extracting Japanese apricot and has been reported to have various effects, including antitumor, anti-inflammatory and liver-supporting functions. MK615 inhibits the release of cytokines, such as TNF-α and IL-6, and may represent a useful therapeutic agent for chronic periodontitis, a condition that is also reported to cause focal infections (18,19). In our facility, we have used nose drops containing MK615 for chronic epipharyngitis for several years.…”
Section: Discussionmentioning
confidence: 99%
“…From ancient times, various parts of P. mume have been used as a health food and a medicinal agent for the treatment of fever, cough, and intestinal disorders. In addition, recent studies have reported that P. mume possesses various pharmacological activities, including inhibition of influenza A virus and motility of Helicobacter pylori, potential sources of free radical scavengers, improvement of blood fluidity, anti-inflammation, and anti-cancer action (21)(22)(23)(24)(25)(26)(27)(28). However, the cellular and molecular mechanisms responsible for the apoptotic effects of P. mume have not yet been determined in human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that P. mume exerts a wide array of pharmacological and biological activities, such as potential sources of free radical scavengers, inhibition of influenza A virus, inhibition of the motility of Helicobacter pylori, improvement of blood fluidity, and inhibition of pro-inflammatory mediators (20)(21)(22)(23)(24)(25). In addition, P. mume has been known to exert anticancer activities in several types of human cancer cells (26)(27)(28). However, cellular and molecular mechanisms underlying the anti-cancer effects of P. mume are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%